'It's all bad news': the first 3 months following a diagnosis of malignant pleural mesothelioma. Issue 7 (18th August 2012) - Arber, Anne; Spencer, Lesley
Abstract Objective This study explores patient's experience during the first 3 months following a diagnosis of malignant pleural mesothelioma. Methods This study uses a grounded theory approach with semi‐structured, face‐to‐face interviews with 10 patients during the first 3 months following diagnosis. Results The key concept that emerged from the data was this: Uncertainty and lack of control leading to emotional, physical and psychosocial distress. Three themes informed the key concept: ' it's all bad news', 'good and bad days' and strategies of amelioration. Patients worked with a short‐term perspective on their illness but worried about the long‐term outcome and the speed of their deterioration. Conclusions Patients receive insufficient psychosocial support during the first 3 months following diagnosis. An early palliative care referral would improve support and referral strategies during the first 3 months of the disease. Copyright © 2012 John Wiley & Sons, Ltd.